Assessment of Acute Pain Management and Associated Factors among Emergency Surgical Patients in Gondar University Specialized Hospital Emergency Department, Northwest Ethiopia, 2018: Institutional Based Cross-Sectional Study. (2nd December 2018) - Andualem, Amare Agmas; Lema, Girmay Fitiwi; Nigatu, Yonas Addisu; Ahmed, Seid Adem
Abstract : Background . Adequate pain management has led to increased comfort in emergency patients, reducing morbidity and improving long term outcomes. Different pain management modalities have been applied in the emergency department among which systemic analgesia is commonly used by preceding a nerve block. Several factors have been associated with poor pain management in low resource setting areas. We aimed to determine pain management modalities and associated factors among emergency surgical patients. Patients and Methods . After obtaining ethical approval from Ethical Review Committee, 203 volunteer patients were enrolled. Institutional based cross-sectional prospective study was conducted from April to May 2018 in Gondar University Specialized Hospital Emergency Department. The severity of pain was measured through Numerical Rating Scale and statistical analysis was performed using SPSS statistical package version 23. Descriptive statistics cross-tab and binary logistics were performed to identify factors related to pain management in emergency department. Results . A total of 203 patients, 138 (68%) males and 65 (32%) females with response rate of 94%, participated in this study. Among them, 66% patients received analgesia within two hours of ED presentation with a mean ± SD of 61.0 ± 34.1 minutes. 70.4 % of patients complained of moderate and severe pain after receiving analgesia. There was a significant difference between trauma and nontrauma patients in mean time of analgesia receiving and residual pain severity (p < 0.001). Age, trauma, physician pain assessment, and severity of pain were the predicting factors for analgesia delivery. Conclusion . The overall practice of pain management in Gondar University Specialized Hospital Emergency Department was not adequate. Therefore, it is vital to implement an objective pain assessment method and documentation of the pain severity to improve pain management practice.